Investigating Students’ Perceptions of Project-Based Learning (PBL) in a TEFL Course: A Case Study in Indonesian Higher Education - Jessica Febrina Haryanto; Siti Mina Tamah; Razanawati Nordin (Universitas Pendidikan Mandalika, 2026)
This study explores the implementation of Project-Based Learning in a Teaching English as a Foreign Language (TEFL) course. Employing a qualitative case study methodology, the research aims to answer two primary research questions: (1) How is TEFL class instruction changed from individual-oriented project learning to group-oriented project learning? and (2) How is the PBL-infused TEFL class instruction perceived by the students? Data were collected through course documentation, classroom observation, and questionnaires distributed to 13 students enrolled in the TEFL course at a faculty of teacher education. Using ADDIE model, the one-semester TEFL course originally constructed with individual-oriented approach was reshaped to emphasize collaborative learning tasks and authentic project outputs. The findings suggest that integrating PBL into the TEFL course provided more diverse learning opportunities for the students to increase their engagement with real-world issues and foster their autonomy, creativity, and active participation. As the transformed course outline gives more time and opportunities for group work, iterative feedback, and authentic assignments, the students perceived collaboration more positively, improved problem-solving skills, and developed professional identity as future educators. Thus, PBL is seen as an alternative pedagogical framework that can support both cognitive and social aspects of the students’ learning. The future implementation of PBL is to be equipped with clear scaffolding strategies to maintain students’ comprehension of the learning processes and maximize the PBL-based instructions. Not only for pedagogical classes, other courses teaching English language skills and components can also implement PBL to give more authentic assignments for the students’ collaborative learning.